Religiusitas Pendengar Dzikir di Media YouTube - Bayu Aribowo (Al-Balagh : Jurnal Komunikasi Islam, 2022)
This article talks about religious experiences through media activities. This activity is related to religious experience, media, the relationship between the senses, experience and subjectivity of sensational forms in giving birth to religious experience. This study tries to see how the YouTube dhikr of a Muslim to make themselves connected with the religious process. In addition, how the user's subjectivity makes the meaning of this dhikr an important thing and helps them towards a religious experience. To answer the question above, the researcher conducted interviews with several selected YouTube dhikr listeners who have different social class backgrounds. In addition, researchers will also analyze several relevant YouTube accounts from the Holy Quran Repeated, Gus Anom, Lafadz Doa, and Muzammil Hasbalallah channel accounts through content postings and dhikr listeners' comments from this study showing that dhikr is interpreted differently for each listener. The process of religiosity for listeners is expressed with symbolic and sensational meanings such as expressions in the language of calm, peace, a form of sensation of belief in help, helping them in life. Listening to dhikr and interpreting dhikr is a subjectivity that makes interpreting dhikr differently. This is because the form of religiosity cannot be understood other than the subject who experiences it. In addition, there are material forms in this YouTube dhikr, such as making remembrance content not only for preaching but for pursuing adsense, there is a subscription to dhikr feature, as well as forms of prayer written through comments, which are mostly worldly.